Organic Geochemistry Studies Aliphatic Fraction Bontang Coal, East Kalimantan - Titik Andriani; R. Y. Perry Burhan (Institut Teknologi Sepuluh Nopember, 2015)
The free radical scavenging activity of Mangiferaindica L. Leaves had been performed. The methanol extract showed the highest 2,2’-azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS) free radical scavenging activity among other extracts. Bioassay guided fractionation was performed and yielded three isolated compounds. Their structures were identified as mangiferin (1), friedelin (2) and lupeol (3). Mangiferin exhibited free radical scavenging activity, with an IC50 value of 12.12 µg/mL in vitro.